THE MEANING OF THE TEPUK TEPUNG TAWAR TRADITION IN ELEMENTARY SCHOOL SCIENCE LEARNING BASED ON MALAY ETHNOPEDAGOGY - Edelweiss Milkana Diva; Anastasya Dewi Ambarwati; Neni Hermita; Rifqa Gusmida Syahrun B. (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study illustrates the meaning of learning based on Malay ethnopedagogy through the integration of the Tepuk Tepung Tawar tradition into the topic of human growth and development in the Science subject for Grade V of Elementary School in Pekanbaru. A descriptive qualitative approach was used, with data collection techniques including observation, classroom discussions, field notes, and student worksheets (LKPD). The results of the study show that the implementation of the Tepuk Tepung Tawar tradition in learning has a positive impact on students’ holistic understanding, covering biological, social, and spiritual aspects. Students were able to connect scientific concepts with cultural experiences, showed increased enthusiasm, and gained an understanding of values such as mutual cooperation, natural balance, and spirituality. These findings affirm that culture-based learning can enhance engagement, deepen the meaning of the material, and holistically shape students' character.